Navigating the river of knowledge: two decades of unraveling global trends in adolescent well-being research - Jafar, Mohd Fairuz; Aziz, Muhammad Noor Abdul; Kasim, Marini; Yanti, Prima Gusti; Asni, Asni; Puspitasari, Nuraini; Purwanto, Sigid Edy (Intelektual Pustaka Media Utama, 2025)
This study examines the global issue of adolescent well-being by conducting a bibliometric analysis of 1,162 publications from the Scopus database, covering the period from 2003 to March 2023. The research aims to identify the most influential contributors, including countries, authors, journals, and key topics, within the field of adolescent well-being. The findings reveal that the USA, the UK, and Italy are the most active countries in this area of research, indicating their strong focus on adolescent well-being issues. Leading authors such as Landsverks and Barth are recognized as highly influential contributors to the field, with their work being frequently cited. The study also highlights prominent academic journals, including Children and Youth Services Review, Child Abuse and Neglect, and Journal of Youth and Adolescence, which have emerged as key platforms for disseminating research on adolescent well-being. These journals have played a crucial role in shaping academic discourse, as evidenced by their high citation counts. In terms of research topics, the analysis identifies major themes such as contributing factors to adolescent well-being and interventions aimed at improving it. These topics have been the focus of extensive research, reflecting the global concern for understanding and addressing the challenges faced by adolescents. The study provides a detailed overview of the current trends in research on adolescent well-being, offering valuable insights for future studies. Overall, the findings contribute to the growing body of literature in this area and underscore the importance of continued research on adolescent well-being at a global level.